Stromal Expression of the Core Clock Gene Period 2 Is Essential for Tumor Initiation and Metastatic Colonization - Shaashua, Lee; Mayer, Shimrit; Lior, Chen; Lavon, Hagar; Novoselsky, Alexander; Scherz-Shouval, Ruth (Frontiers in Cell and Developmental Biology, 2020)
The circadian clock regulates diverse physiological processes by maintaining a 24-hour gene expression pattern. Genetic and environmental cues that disrupt normal clock rhythms can lead to cancer, yet the extent to which this effect is controlled by the cancer cells versus non-malignant cells in the tumor microenvironment (TME) is not clear. Here we set out to address this question, by selective manipulation of circadian clock genes in the TME. In two different mouse models of cancer we find that expression of the core clock gene Per2 in the TME is crucial for tumor initiation and metastatic colonization, whereas another core gene, Per1, is dispensable. We further show that loss of Per2 in the TME leads to significant transcriptional changes in response to cancer cell introduction. These changes may contribute to a tumor-suppressive microenvironment. Thus, our work unravels an unexpected protumorigenic role for the core clock gene Per2 in the TME, with potential implications for therapeutic dosing strategies and treatment regimens.